Behavior of Soil-structure interfaces under cyclic loading for large numbers of cycles: Application to piles - Bekki, Hadj; Tali, Brahim; Canou, Jean; Dupla, Jean-Claude; Bouafia, Ali (Journal of Applied Engineering Science & Technology; Vol 1 No 1 (2014), 2014)
Pile foundations are usually subjected to cyclic loading which can be either environmental or industrial. Loading and unloading sequences of the pile cause very significant variation in the behavior of the pile-soil system and generate degradation of the bearing capacity and an accumulation of irreversible displacement. The paper presents a study of the behavior of piles subjected to axial cyclic loading for large numbers of cycles using a physical modeling approach in a calibration chamber. To focus on the degradation of the friction in soil-pile interface, the experiments are carried out in two-way displacement–controlled tests. Firstly, The experimental set-up was presented, then the typical results of the evolution of skin friction under cyclic loading. The results indicate that the application of a large number of cycles to the pile, the skin friction decrease initially then increase continually up to the end of the cyclic sequence. It can be concluded that the phase of friction reinforcement is due to a partially constrained dilatancy phenomenon of the sand within the interface zone. Résumé : Généralement les pieux sont soumis à des sollicitations cycliques qui peuvent être de type environnemental ou industriel. Le chargement et le déchargement du pieu provoquent une évolution très significative du comportement du système pieu- sol et engendrent une dégradation de la capacité portante ainsi que l’accumulation des déplacements irréversibles. L’article présente une étude du comportement des pieux chargés axialement, par une modélisation physique en chambre d’étalonnage, sous l’effet d’un chargement cyclique à grand nombre de cycles. Les essais ont été réalisés à déplacement contrôlé de type alterné afin de maître en évidence le phénomène de dégradation du frottement à l’interface sol-pieu. On présente tout d’abord le dispositif expérimental utilisé, puis les résultats typiques sous l’effet du chargement cyclique en s’intéressant, plus particulièrement, à l’évolution du frottement au niveau de l’interface sol-pieu. L’analyse des résultats trouvés nous a permis de conclure qu’en appliquant un chargement cyclique à grand nombre de cycles sur le pieu, le frottement latéral subira au début une dégradation puis une augmentation qui continuera jusqu’à la fin de la séquence cyclique. Ce renforcement observé du frottement latéral est dû à la forte dilatance partiellement empêchée de la zone d’interface sol-pieu. Mots clés : Chambre d’étalonnage, pieu, sol, interface, frottement latéral, chargement cyclique, dégradation.
Keywords: Calibration chamber, pile, soil, interface, skin friction, cyclic loading